SYSTEM OF ECONOMIC ANALYSIS INDICATORS FOR PLANNING INTEGRATION COMPANIES - M. Katalkina (Вестник университета)
The issue of economic analysis of planning integration companies is considered in the article and the choice of indicators that can affect decision making about integration particularly. The author suggest a system of economic analysis indicators for planning integration companies which allows to identify the possibility and necessity of the integration and set its main goals and objectives. The results of evaluation can be used in selecting a target company for integration.